Accelerating nutrition for a food systems transformation: HarvestPlus 2022 annual report - HarvestPlus (International Food Policy Research Institute, 2023)
HarvestPlus improves nutrition and health by working with partners worldwide to develop and promote biofortified crops that are rich in vitamins and minerals, and providing leadership on biofortification evidence and technology.